It's not fair! - Hautzig, Deborah (New York : Random House/Children's Television Workshop, 1986)
When irresponsible Ernie seems to be taking all the credit for Bert and threatens their friendship
Featuring Jim Henson's Sesame Street Muppets
Keywords: Anger-Fiction; Friendship-Fiction; Puppets-Fiction